Santa : A Novel of Mexico City - Gamboa, Federico, 1864-1939 (Book collections on Project MUSE., 2010)
This enduring classic of Mexican literature traces the path to ruination of a country girl, Santa, who moves to Mexico City after she is impregnated and abandoned by her lover and subsequently shunned by her family. Once in the city, Santa turns to prostitution and soon gains prominence as Mexico City's most sought-after courtesan. This evocative novel--justly famous for its vividly detailed depiction of the cityscape and the city's customs, social interactions, and political activities--assumed singular importance in Mexican popular culture after its original publication in 1903.